PEMBINGKAIAN BERITA KEBAKARAN DEPO PERTAMINA PLUMPANG DI CNNINDONESIA.COM DAN REPUBLIKA.CO.ID - Hanifa Nurul Hidayat; Wahyudi Marhaen Pratopo (Jurnal Komunikasi & Media Digital, 2024)
This research concerns the framing of Pertamina Plumpang Depot fire news on CNNIndonesia.com and Republika.co.id on 3-10 March 2023. The research used a qualitative method with framing theories. The data analyses in this research are conducted by using Pan and Kosicki's framing analysis model, which is based on four structures, namely syntactic, script, thematic, and rhetoric. The results of the research have shown that CNNIndonesia.com and Republika.co.id have differences in framing the news of the 2023 Pertamina Plumpang Depot fire. CNNIndonesia.com frames the news by criticizing the government for the location of the fire that claimed many victims, which was the result of the government's indecisiveness and negligence, as well as the reactive solutions taken by Pertamina. CNN Indonesia prioritizes the value of independence in its news content without any vested interests. Meanwhile, Republika.co.id frames the news by focusing on efforts taken by the government and Pertamina. Republika has not been able to fully maintain independence in its news reporting because the media is involved in the vested interests of its owner.